Adaptação transcultural semântica e idiomática de um instrumento de adesão medicamentosa para população idosa - Silva, Renata Soares da (2020)
The objective of this research was to carry out a Transcultural Adaptation of an instrument that assesses the barriers to medication adherence, the Adhesion Barriers Questionnaire (ABQ), written first in English. This adaptation occurs for Brazilian Portuguese, with necessary changes for elderly population understand the items. The methodology used followed the four-step procedure: translation of the original scale, back-translation of the translated scale, review by the Committee of Experts and pre-test with sampling of elderly patients. After translations and backtranslations, previous versions were analyzed by Committee of Experts, who made adjustments in the writing and understanding of items with the most appropriate language for a better understanding of the target population (elderly), taking into account characteristics of the population, such as literacy, visual and cognitive difficulties and self-specified format for the interview. The application of ABQ occurred in two stages (pre-test and pilot study); in both, the probing technique was performed. The difficulties encountered in the pre-teste were and modified for the pilot study. The sample oh the pre-teste and pilot study was 30 patients seen in each phase, aged 60 years or over, both sexes. These patients are followed up by the Primary Care System of the Unified Health System in a small port city in western Paraná. Of the interviewees, 58,33% were female, 68,33% had incomplete Elementary Education and 52,56% had Primary Essential Hypertension as their main diagnosis. For reliability analysis, Cronbach‟s and item-total. The most prevalent adherence barrier among participants referred to item 9 and the unintentional subscale was present in 43.33% of the responses presented. The Brazilian version of the ABQ questionnaire an important instrument adapted to the Brazilian linguistic and cultural context, with modifications aimed at the elderly population. Future research will investigate the psychometric properties oh this questionnaire‟s validation. And yet, this Brazilian version can be validated for other regions, in view of the diversity of cultures that Brazil presents.